Methodical Framework of the Support and Decision-making System for the Collection and Disposal of Organic Raw Materials - Sergei Shvorov; Dmitry Komarchuk; Peter Ohrimenko; Dmitry Chyrchenko (Energy Engineering and Control Systems)
Topical and important issue is the national problem of introduction of biomethane production and the Ukrainian gas transportation system. This problem can be addressed through the use of information technology based on the monitoring and forecasting the prospective base of knowledge organic raw materials and optimal scheduling of seeding, harvesting and conversion of crops and other organic waste into biogas energy. Based on the analysis of problems of management and factors affecting the efficiency of the biogas complexes (BGC) functional structure of decision support systems that is best adapted to the challenges of planning for the organization cultivation, collection and processing of organic raw materials into biomethane has been developed.